Acute spasticity in malignant MCA stroke: a case report and review of literature - Muhammad Faizan (12710607) (2025)
Malignant Middle cerebral artery (MCA) infarction is characterized by rapid neurological deterioration due to cerebral edema. Spasticity, a common sequela of stroke, typically occurs days to weeks after the initial event. However, an acute onset of spasticity at presentation is extremely rare. We report a case of a 40-year-old male patient who presented with spasticity accompanied by aphasia and decreased consciousness. Left MCA occlusion was demonstrated on Computed tomography (CT) angiography. Cerebral edema developed rapidly, requiring decompressive hemicraniectomy (DH). The patient was a known smoker with androgenic anabolic steroid use. This case represents a rare presentation of malignant MCA infarction with acute spasticity and adds a unique aspect to the clinical spectrum of stroke presentation. This case emphasizes the need for awareness of atypical stroke presentation and the potential role of anabolic steroids in stroke risk. Other Information Published in: Oxford Medical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/omcr/omaf114